The piano music of Peter Klatzow : a stylistic analysis of selected works - Odendaal, Andries Albertus (College of Music, 2015)
The piano music of Peter James Leonard Klatzow forms an integral part of his musical output. An analysis of these works may provide useful insight into the compositional style of this South African composer. Jan LaRue's theory of stylistic analysis formed the inspiration for the analytical approach of the thesis, and the main focus of this analysis is the 1994 composition, From the Poets. This work is analysed in terms of use of sound, harmony and melody in order to attempt an understanding of how these elements impact and contribute to the sense of structure. Other works that have been completed since 1980 are analysed in terms of the main motivic and harmonic material, with occasional reference to other musical parameters that are important for an understanding of the musical discourse.